Hammertoe Correction with Wire Fixation of Varying Length. Issue 1 (January 2022) - Mayolo, Patrick; Kress, Kristin L.; Kang, Paul; Jaffe, David E.
Category: Midfoot/Forefoot; Lesser Toes Introduction/Purpose: Hammertoe deformities are commonly encountered and frequently require surgical intervention for pain relief and shoewear accommodation. Various techniques exist for surgical management, but proximal interphalangeal (PIP) joint fusion with Kirschner (K) -wire fixation remains an inexpensive, popular treatment. The decision to place a K wire that spans the metatarsophalangeal (MTP) joint versus only fixating the digit through the proximal phalanx is entirely dependent on provider preference and situational context. This study was performed to evaluate the effect of length of wire fixation on clinical outcomes after hammertoe reconstruction. Methods: A retrospective review of all hammertoe reconstructions by a single fellowship trained foot and ankle surgeon from 2017-2021 was performed. Hammertoe reconstructions involved PIP arthrodesis with double wire fixation and other supplemental balancing procedures as indicated. Pins were routinely removed at between 5-6 weeks and protected heel weightbearing was generally advised. Wire length was chosen at the discretion of the surgeon intraoperatively. Patients were excluded if no radiographic follow-up was available after pin removal. Patient outcomes were evaluated with radiographs and clinic notes to assess pin length, pin complications/breakage, return to the OR, MTP congruency, and PIP union rate. A logistic regression was performed to determine the odds ratio for digit congruency and non-union status. Results: 88 toes (45 patients) underwent hammertoe reconstruction with K wire fixation. Of these toes, 47 had wires that spanned the MTP and 41 that did not. There were 65 congruent MTP joints and 23 incongruent joints. 16 of the incongruent joints were pinned across the MTP while 31 in the congruent group were pinned. One toe in the MTP group required return to the OR for removal of a broken wire, compared to zero in the phalanx group (p=1.0). No pins broke in the phalanx group, compared to 3 in the MTP group (p=0.25). One toe in the proximal phalanx group had their pins pull out early but no return to the OR was needed. There were 26 (63.4%) PIP radiographic nonunions, compared to 21 (44.7%) in the MTP group (p=0.12). Conclusion: Wire failure was a rare occurrence in either group. Breakage only occurred in the MTP group, but only required one surgical intervention for removal. Pinning the MTP may allow for improved deformity correction and increased stability of the hammertoe reconstruction. Pin breakage can occur, but it may be of little clinical significance. The increased stability and control of MTP correction may be worth the potential risk of pin breakage. Pin breakage may be avoided potentially by using thicker wires, earlier removal, and protected weightbearing.